2014
DOI: 10.1080/10410236.2014.974126
|View full text |Cite
|
Sign up to set email alerts
|

Telling Stories, Saving Lives: Creating Narrative Health Messages

Abstract: Increasingly, health communication practitioners are exploring the use of narrative storytelling to convey health information. For this study, a narrative film was produced to provide information about the Human Papillomavirus (HPV) and cervical cancer prevention. The storyline centered on Lupita, a young woman recently diagnosed with HPV who informs her family about HPV and the availability of the HPV vaccine for her younger sister. The objective was to examine the roles of identification with characters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 38 publications
4
73
1
4
Order By: Relevance
“…The current study supports research that video narratives highlighting HPV susceptibility, vaccine safety, and overcoming barriers to vaccination resonate with college women (Hopfer, 2011). Our findings emphasize the importance of increasing perceptions of susceptibility and knowledge of HPV through narrative involvement and relevance of campaign messages (Frank et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…The current study supports research that video narratives highlighting HPV susceptibility, vaccine safety, and overcoming barriers to vaccination resonate with college women (Hopfer, 2011). Our findings emphasize the importance of increasing perceptions of susceptibility and knowledge of HPV through narrative involvement and relevance of campaign messages (Frank et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…Narratives, or stories about individuals – often used by the news media, policymakers, and advocates to illustrate and engage audiences in policy issues(Murphy, Frank et al 2013, Frank, Murphy et al 2015, Niederdeppe, Heley et al 2015) – can be systematically varied by researchers to test specific messages’ influence on public attitudes. Policy actors have long used narratives to illustrate policy problems and potential solutions.…”
Section: Introductionmentioning
confidence: 99%
“…This type of somatic understanding and empathy is described by Finlay (2006) as 'embodied intersubjectivity' where, for example, a researcher may experience embodied feelings that seem to mirror those of her/his interviewee. Furthermore, Frank et al (2015) found that the more directly relevant a narrative was felt to be to a person's own life, the more effective the narrative in stimulating reflection and behaviour change.…”
Section: Empathy and Somatic Empathymentioning
confidence: 99%